Tone Language Fluency Impairs Pitch Discrimination - Peretz, Isabelle; Nguyen, Sebastien; Cummings, Stephanie (Frontiers in Psychology, 2011)
Here we present evidence that native speakers of a tone language, in which pitch contributes to word meaning, are impaired in the discrimination of falling pitches in tone sequences, as compared to speakers of a non-tone language. Both groups were presented with monotonic and isochronous sequences of five tones (i.e., constant pitch and intertone interval). They were required to detect when the fourth tone was displaced in pitch or time. While speakers of a tone language performed more poorly in the detection of downward pitch changes, they did not differ from non-tone language speakers in their perception of upward pitch changes or in their perception of subtle time changes. Moreover, this impairment cannot be attributed to low musical aptitude since the impairment remains unchanged when individual differences in musical pitch-based processing is taken into account. Thus, the impairment appears highly specific and may reflect the influence of statistical regularities of tone languages.